NAVIGATING BETWEEN ETHNIC AND RELIGIOUS IDENTITY: HERITAGE LANGUAGE MAINTENANCE AMONG YOUNG AUSTRALIANS OF INDONESIAN ORIGIN - Muslim, Ahmad Bukhori; Brown, Jillian R. (Universitas Pendidikan Indonesia, 2016)
For ethnic minority groups, speaking a heritage language signifies belonging to their country of origin and enriches the dominant culture. The acculturation of major ethnic groups in Australia – Greek, Italian, Chinese, Indian and Vietnamese – has been frequently studied, but a minor one like Indonesian has not. Through semi-structured interviews at various places and observations at cultural events, the study explores the contextual use, meaning and perceived benefits of Bahasa Indonesia (Indonesian language) among Indonesian families and how this practice influences the young participants’ (18-26 years old) identification with Indonesia, the origin country of their parents, and Australia, their current culture of settlement. The findings suggest that Bahasa Indonesia serves as a marker of ethnic and religious identity glued in family socialization. Parents believe that not only does the language signify their Indonesian ethnic identity, but also provides a means for socializing family values, and is beneficial for educational purposes and future career opportunities. However, parents face a dilemma whether to focus on ethnic or religious identity in socializing the use of Bahasa Indonesia. Interestingly, most young participants demonstrate a more global worldview by embracing both Indonesian and Australian values. How religious identity relates to more global worldview should be addressed more comprehensively in future studies.